Fucosyltransferase 2 (FUT2) non-secretor status and blood group B are associated with elevated serum lipase activity in asymptomatic subjects, and an increased risk for chronic pancreatitis: a genetic association study. Issue 4 (15th July 2014) - Weiss, Frank Ulrich; Schurmann, Claudia; Guenther, Annett; Ernst, Florian; Teumer, Alexander; Mayerle, Julia; Simon, Peter; Völzke, Henry; Radke, Dörte; Greinacher, Andreas; Kuehn, Jens-Peter; Zenker, Martin; et al.
Abstract : Objective: Serum lipase activities above the threefold upper reference limit indicate acute pancreatitis. We investigated whether high lipase activity—within the reference range and in the absence of pancreatitis—are associated with genetic single nucleotide polymorphisms (SNP), and whether these identified SNPs are also associated with clinical pancreatitis. Methods: Genome-wide association studies (GWAS) on phenotypes 'serum lipase activity' and 'high serum lipase activity' were conducted including 3966 German volunteers from the population-based Study-of-Health-in-Pomerania (SHIP). Lead SNPs associated on a genome-wide significance level were replicated in two cohorts, 1444 blood donors and 1042 pancreatitis patients. Results: Initial discovery GWAS detected SNPs within or near genes encoding the ABO blood group specifying transferases A/B ( ABO ), Fucosyltransferase-2 ( FUT2 ), and Chymotrypsinogen-B2 ( CTRB2 ), to be significantly associated with lipase activity levels in asymptomatic subjects. Replication analyses in blood donors confirmed the association of FUT-2 non-secretor status (OR=1.49; p=0.012) and ABO blood-type-B (OR=2.48; p=7.29×10 −8 ) with high lipase activity levels. In pancreatitis patients, significant associations were found for FUT-2 non-secretor status (OR=1.53; p=8.56×10 −4 ) and ABO -B (OR=1.69, p=1.0×10 −4 ) with chronic pancreatitis, but not with acute pancreatitis. Conversely, carriers of blood group O were less frequently affected by chronic pancreatitis (OR=0.62; p=1.22×10 −05) and less likely to have high lipase activity levels (OR=0.59; p=8.14×10 −05 ). Conclusions: These are the first results indicating that ABO blood type-B as well as FUT2 non-secretor status are common population-wide risk factors for developing chronic pancreatitis. They also imply that, even within the reference range, elevated lipase activities may indicate subclinical pancreatic injury in asymptomatic subjects.